2021
DOI: 10.1029/2020gb006798
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variability of Air‐Sea CO2 flux in the Western Tropical North Atlantic Influenced by the Amazon River Plume

Abstract: The partial pressure of carbon dioxide (pCO2) was surveyed across the Amazon River plume and the surrounding western tropical North Atlantic Ocean (15–0°N, 43–60°W) during three oceanic expeditions (May–June 2010, September–October 2011, and July 2012). The survey timing was chosen according to previously described temporal variability in plume behavior due to changing river discharge and winds. In situ sea surface pCO2 and air‐sea CO2 flux exhibited robust linear relationships with sea surface salinity (SSS; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 61 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…Thus, both the increase in DIC from remineralization and the decrease in TA from dilution lead to an increase in sea surface pCO 2 , but this is not sufficient to counteract the pCO 2 drawdown by primary production. Therefore, photosynthesis is the main driver of sea surface pCO 2 drawdown in the ARP (Figure S8 in Supporting Information S1), as has been suggested in a number of previous studies (Bonou et al, 2016;Körtzinger, 2003;Lefèvre et al, 2017;Louchard et al, 2021;Mu et al, 2021). Moreover, both CO 2 solubility and calcium carbonate dissolution by riverine waters likely exert some influence on the marine carbonate system.…”
Section: Sea-air Co 2 Exchanges In the Amazon River Plumementioning
confidence: 57%
See 3 more Smart Citations
“…Thus, both the increase in DIC from remineralization and the decrease in TA from dilution lead to an increase in sea surface pCO 2 , but this is not sufficient to counteract the pCO 2 drawdown by primary production. Therefore, photosynthesis is the main driver of sea surface pCO 2 drawdown in the ARP (Figure S8 in Supporting Information S1), as has been suggested in a number of previous studies (Bonou et al, 2016;Körtzinger, 2003;Lefèvre et al, 2017;Louchard et al, 2021;Mu et al, 2021). Moreover, both CO 2 solubility and calcium carbonate dissolution by riverine waters likely exert some influence on the marine carbonate system.…”
Section: Sea-air Co 2 Exchanges In the Amazon River Plumementioning
confidence: 57%
“…This leads to a net increase in p CO 2 over the whole NEC (Figure 3) during maximum NBC retroflection, despite the nutrient‐ and carbon‐enriched waters from the Amazon River (Lefèvre et al., 2020). During the dry season, instead of being transported to the east, the waters from the Amazon River are mainly advected to the northwest, decreasing p CO 2 in the NEC sub‐region due to high primary productivity (Bonou et al., 2016; Ibánhez et al., 2015; Louchard et al., 2021; Mu et al., 2021), hence intensifying the biological uptake of CO 2 (Figure 2a). Indeed, model estimates suggested that without the influence of the Amazon River, much of the western Tropical Atlantic Ocean, including part of the NEC sub‐region, would be a CO 2 source year‐round (Louchard et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows that waters with a SST of 26.5°C and SSS between 35-36 can either be rich in Chla and have a high fCO2 or low in Chla and have a low fCO2. Waters rich in detrital material tends to limit the phytoplankton growth and microbial respiration of riverine material on the continental shelf likely dominates (Aller & Blair, 2006;Medeiros et al, 2015;Mu et al, 2021). This relationship is analyzed in more detail for the different water masses identified in the region in parts 3.2. and 3.3.…”
Section: Reconstruction Of Fco2 From Satellite Mapsmentioning
confidence: 99%